HUBUNGAN KONSEP DIRI DENGAN MOTIVASI BERPRESTASI PADA SISWA AKSELERASI DAN SISWA REGULER - Feby Armelia Putri; Sesilia Monika; Ninawati Ninawati (Provitae: Jurnal Psikologi Pendidikan, 2016)
The concept of self is how individuals perceive or judge him, an assessment of confidence in himself, psychologically or socially good physical characteristics, or capabilities. The formation of self-concept can be positive or negative direction. While the achievement motivation is the impetus that exist within the individual's success and aims to successfully achieve a feat. Someone underachievers is someone who sees himself as a person who is less adequate than in others. Someone underachievers tend to express more feelings of negative self compared with someone who has high academic achievement. The aim of this research to determine the relationship of self-concept and achievement motivation in students acceleration and regular students. Research conducted at SMA N XYZ in the city of Serang Banten. The subjects of this research were 96 students in class XI, ie 32 on the acceleration students and 64 regular students. retrieval techniques using non-probability sampling (convenience). Methods of data collection using a scale of self-concept and achievement motivation. Spearman correlation analysis result there is a significant relationship between self-concept and achievement motivation r = 0.556 and p = 0.000, thus it can be concluded that there is a relationship self-concept and achievement motivation in students acceleration and regular students.Keywords: Self-concept, achievement motivation, Student acceleration, regular student